1996
DOI: 10.1038/ng0196-31
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of non-insulin dependent diabetes mellitus in the GK rat

Abstract: Non-insulin dependent diabetes mellitus (NIDDM) is a major public health problem, but its aetiology remains poorly understood. We have performed a comprehensive study of the genetic basis of diabetes in the Goto-Kakizaki (GK) rat, the most widely used animal model of non-obese NIDDM. The genetic dissection of NIDDM using this model has allowed us to map three independent loci involved in the disease. In addition, we identify a major factor affecting body weight, but not glucose tolerance, on chromosome 7 and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
159
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(172 citation statements)
references
References 29 publications
8
159
0
5
Order By: Relevance
“…These results confirm reports of significantly elevated concentrations of plasma cholesterol and triglycerides in GK rats when compared with Wistar controls [9,29]. Even though the lipid QTLs reported here appear to map to different locations than previously identified GK diabetes and obesity QTLs [11,12], we cannot rule out the possibility that the altered regulation of plasma triglycerides and HDL cholesterol in GK rats has a direct impact on diabetes severity and progression. Further genetic studies of blood pressure regulation in crosses of the GK rat will be crucial to our understanding of the aetiological relationships between pathophysiological components of the metabolic syndrome in this model.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These results confirm reports of significantly elevated concentrations of plasma cholesterol and triglycerides in GK rats when compared with Wistar controls [9,29]. Even though the lipid QTLs reported here appear to map to different locations than previously identified GK diabetes and obesity QTLs [11,12], we cannot rule out the possibility that the altered regulation of plasma triglycerides and HDL cholesterol in GK rats has a direct impact on diabetes severity and progression. Further genetic studies of blood pressure regulation in crosses of the GK rat will be crucial to our understanding of the aetiological relationships between pathophysiological components of the metabolic syndrome in this model.…”
Section: Discussionsupporting
confidence: 54%
“…Genetic studies in this model have primarily aimed at investigating the inheritance of glucose intolerance and altered insulin secretion and defining regions of the GK genome that contribute to diabetes susceptibility. Independent genetic studies in F2 cohorts derived from the GK rat and normoglycaemic Brown Norway (BN) or Fisher rats have demonstrated the polygenic control of diabetes-related phenotypes [11,12]. At least six different quantitative trait loci (QTLs) control fasting glycaemia and insulinaemia, glucose tolerance, glucose and arginine-stimulated insulin secretion, body weight and adiposity in a GK×BN cross [12].…”
mentioning
confidence: 99%
“…3 The Goto-Kakizaki (GK) rat exhibits a markedly reduced glucose-induced insulin release in vivo, and in the isolated perfused pancreas and isolated islets. [4][5][6][7] A previous study from our laboratory demonstrated that the AC3 mRNA was overexpressed in the pancreatic islets of GK rat, which was caused by two point mutations at positions À28 A/G and À358 A/C of the promoter region. 8 The insulinotropic effect of forskolin in GK rat islets is associated with an enhanced cAMP generation and with overexpression of AC3 mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…The search for morbid genes using a quantitative trait locus (QTL) approach has led to identification of six independently segregating-loci-containing genes involved in glucose homeostasis in GK/Par rats [12]. The same conclusion was drawn by Galli et al [19] using GK/Sto rats. Besides the role of GK susceptibility loci, the possibility exists that the GK maternal diabetic environment per se causes early changes in the structure and function of several organs in the offspring, including the endocrine pancreas, and has profound influence on glucose handling by the fetus, which persists into adult life and the subsequent generation of offspring.…”
Section: Discussionmentioning
confidence: 72%